Microstructural and transport properties of LaNiO3-delta films grown on Si(111) by chemical solution deposition - Escote, M. T.; Pontes, F. M.; Leite, E. R.; Varela, José Arana [UNESP]; Jardim, R. F.; Longo, Elson [UNESP] (Elsevier B.V., 2003)
Electrically conductive LaNiO3-delta (LNO) thin films with typical thickness of 200 nm were deposited on Si (111) substrates by a chemical solution deposition method and heat-treated in air at 700 degreesC. Structural, morphological, and electrical properties of the LNO thin films were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), field-emission scanning electron microscopy (FEG-SEM), and electrical resistivity rho(T). The thin films have a very flat surface and no droplet was found on their surfaces. The average grain size observed by AFM and FEG-SEM was approximately 100 nm in excellent agreement with XRD data. The rho(T) data showed that these thin films display a good metallic character in a large range of temperature. These results suggest the use of this conductive layer as electrode in the integration of microelectronic devices. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: thin films; electrical properties; chemical solution deposition; atomic force microscopy (AFM)